Imagining a Postnational World – Hegemony and Space in Modern China - Matten, Marc (Brill, 2016)
This book analyzes the historical significance of rivaling concepts of world order in 20th century East Asia. Since the arrival of European imperialism in 19th century – coupled with its different schools of political philosophy and international law – China has struggled to combine ideas on national sovereignty, spatiality and hegemony in its quest of either imitating or replacing European norms of world order. By analyzing Chinese visions of regional and international order and comparing them with Japanese proposals of that era, this book discusses in detail the relationship of territoriality and political rule, discourses of amity and enmity, and finally the role of hegemoniality in the process of imagining a possible postnational world in 21st century East Asia and beyon
Keywords: Asian history; history of international relations; history of pan-Asianism; national cartography in China; spatial turn